Nonlinear Vibration of Microbeams Based on The Elastics Foundation Using High-Order Energy Balance Method and Global Error Minimization Method - V. Hieu, D (International Journal of Engineering and Technology, 2018)
In this paper, nonlinear vibration of microbeams based on the nonlinearÂ elasticÂ foundationÂ isÂ investigated. TheÂ equationÂ of motion of microbeams based on three-layered nonlinear elastic medium (shear, linear and nonlinear layers) is described by the partial differential equation by using the modified couple stress theory.Â The equation of motion of microbeams is transformedÂ into the ordinary differential equation by using Galerkin method. The high-order Energy BalanceÂ method and the high-order Global Error Minimization method areÂ usedÂ toÂ getÂ theÂ frequency â€“Â amplitude relationshipsÂ forÂ theÂ nonlinearÂ vibrationÂ ofÂ microbeamsÂ with pinned-pinnedÂ andÂ clamped-clampedÂ endÂ conditions. Comparisons between the present solutions and the privious solutionsÂ showÂ theÂ accuracyÂ ofÂ theÂ obtainedÂ results.Â Â